Cycle-dependent in vitro wear performance of dental ceramics after clinical surface treatments. (January 2016) - Preis, Verena; Grumser, Katharina; Schneider-Feyrer, Sibylle; Behr, Michael; Rosentritt, Martin
Abstract: Aim: To investigate the two-body wear performance of dental ceramics after different clinical surface treatments as a function of number of wear cycles. Material and methods: Standardized specimens ( n =72/material) were prepared from two different zirconia ceramics, a veneering porcelain, and a lithiumdisilicate glass ceramic. Specimens were progressively glazed, ground, and polished. After each treatment step 24 specimens per material were kept at the obtained surface state. Steatite and human enamel specimens served as reference materials. Two-body wear tests were performed with steatite spheres as antagonists in a pin-on-block design (50 N, 1.6 Hz, lateral movement: 1 mm, mouth opening: 2 mm) under simultaneous thermal cycling (5/55 °C, 2 min/cycle). For investigating the dynamic evolution of the wear process, 9 groups per material ( n =8/group) were defined, differing in surface state (glazed, ground, and polished) and number of chewing cycles (40T, 80T, and 120T; T: ×1000): glazed 40T, glazed 80T, glazed 120T, ground 40T, ground 80T, ground 120T, polished 40T, polished 80T, polished 120T. Surface roughness, wear depth of the specimens and relative wear area of the steatite antagonists were determined using an optical 3D laser scanning microscope. SEM evaluation was done. Mean values and standard deviations were calculated and statistically analyzed (one-way ANOVA, post-hoc Bonferroni, α =0.05). Results: Veneering and lithiumdisilicate ceramics showed higher wear depths than zirconia ceramics ( p <0.05). Wear of veneering and lithiumdisilicate ceramics and their antagonists increased with wear cycles but was only marginally influenced by the initial surface state. Wear of zirconia was not influenced by wear cycles but antagonists of zirconia showed a cycle-dependent wear increase. Polished zirconia surfaces showed lowest wear for material and antagonist. Wear mechanism of common ceramics was characterized by abrasive wear. Zirconia in contrast showed a superficial cyclic shifting of worn material of the antagonist. Conclusions: Wear of zirconia and standard ceramics showed different wear performances, strongly influenced by surface treatments as well as number of wear cycles. Graphical abstract: Highlights: Glass ceramics and their antagonists showed a cycle-dependent wear increase. Zirconia wear rates resulted from a cyclic shifting of worn antagonistic debris. Surface state and wear rates of glass ceramics approximated during wear simulation. Zirconia surface state as widely constant parameter was of high importance. Lowest wear of material and antagonist was found for polished zirconia.